PENDIDIKAN PENGELOLAAN SAMPAH DI KELURAHAN SAMPANGAN KECAMATAN GAJAH MUNGKUR - Deasy Ratna Sari (Jurnal Geografi : Media Informasi Pengembangan dan Profesi Kegeografian, 2015)
This study aimed to: find out about the educational background of awareness of waste management in RW 02 SubSampangan, knowing awareness in waste management RW 02, knowing the relationship of public awareness onwaste management to the education level of the residents of RW 02 and determine the role of the presence of KSMNgudi Kamulyan , as well as the existence of the concept of Geography assessed. The location of this study in RW02 Sub Sampangan Gajah Mungkur Semarang. The samples taken were 25 % of the population of 163 families,the obtained results of the number of samples is 41 families. The technique used to determine the number ofsamples is Disproportionet Stratified Random Sampling. Data collection techniques used are observation, survayand interviews. Methods of data analysis that is Table Cross (Bivariate). The level of education and awareness inwaste management obtained from interviews, while the relationship waste management awareness in theeducational level is Table Cross (Bivariate). Based on the results of this study concluded that non-formaleducation and socialization conducted training on the management of organic waste and inorganic highestpercentage in the awareness of citizens in waste management 13 ( 31.71 % ). Educational background have thehighest awareness is high as many as 6 people ( 14.7 % ). The role of the presence of KSM Kamulyan Ngudi high( 97.6 % ).